Fish consumption and risk of prostate cancer or its mortality: an updated systematic review and dose–response meta-analysis of prospective cohort studies - Eshaghian, Niloofar; Heidarzadeh-Esfahani, Neda; Akbari, Hakimeh; Askari, Gholamreza; Sadeghi, Omid (Frontiers in Nutrition, 2023)
Since the release of the last meta-analysis on the association between fish intake and prostate cancer risk, several cohort studies have been published. Moreover, none of the previous metaanalyses examined the dose-response association between fish intake and prostate cancer.Therefore, the current dose-response meta-analysis was conducted to summarize available findings on the associations of fish intake with the risk of prostate cancer in men. Online databases of PubMed, Scopus, and Web of Science were systematically searched up to September 2022. We included prospective cohort studies that examined the associations of fish intake with the risk of prostate cancer (total, localized, and advanced prostate cancer), its mortality, and cancer progression. Summary relative risks (RR) and 95% confidence intervals (CI) were calculated for the highest versus lowest categories of fish intake using random-effects models. Also, linear and non-linear dose-response analyses were conducted. In total, 25 prospective cohort studies, recruiting 1,216,474 men, were included in the systematic review, and 22 studies were included in the meta-analysis. During the follow-up periods, ranging from 6 to 33 years, a total of 44,722 cases of prostate cancer were recorded. The comparison between the highest and lowest intakes of total fish revealed the summary RRs of 0.97 (95% CI: 0.86-1.10) for total, 1.01 (95% CI: 0.91-1.13) for advanced, and 0.90 (95% CI: 0.72-1.12) for localized prostate cancer, indicating no significant association. Moreover, the summary RR was 0.55 (95% CI: 0.33-0.92) for prostate cancer mortality and 0.84 (95% CI: 0.65-1.10) for prostate cancer progression, indicating an inverse association between fish intake and prostate cancer mortality. Also, in the dose-response analyses, each 20 gram/day increase in total fish intake was associated with a 12% lower risk of prostate cancer mortality. Our findings support the protective association between total fish intake and the risk of prostate cancer mortality. 4